Australia and Canada in Afghanistan : perspectives on a mission - Maley, William, 1957-; Cunningham, Jack (Historian) (Dundurn Press, 2015)
Afghanistan is a long way from both Canada and Australia, but from 2001, fate conspired to bring the three countries together. Following the attacks of September 11, 2001, Australia and Canada joined the U.S. and other Western allies in attacking al-Qaeda bases in Afghanistan. Operation Enduring Freedom began on October 4, 2001, but this was only the beginning of a much longer engagement in Afghanistan for both Canada and Australia, with a legacy much more ambiguous than the initial campaign had promised. Australia and Canada in Afghanistan: Perspectives on a Mission offers twelve essays from distinguished experts and decision-makers involved in the war. Wide-ranging in scope, their work offers fresh analyses of the Afghan War and on Australia's and Canada's contributions to it.
Keywords: Operation Enduring Freedom, 2001-2014.; Afghan War, 2001-2021 -- Participation, Australian.; Afghan War, 2001-2021 -- Participation, Canadian.; Afghan War, 2001-2021 -- Campaigns.; Opération Liberté immuable, 2001-2014.; Guerre en Afghānistān, 2001-2021 -- Campagnes et batailles.; Australia & New Zealand.; HISTORY.; Canada.; Military.; Military campaigns; Military participation -- Australian; Military participation -- Canadian; 2001